An empirical analysis of competition and efficiency in the medical scheme market in South Africa - Dzinotyiwei, Chido (Graduate School of Business (GSB), 2025)
In South Africa, pre-funded healthcare products are dominated by medical schemes and this market segment is regulated by the Council for Medical Schemes (CMS) which abides by the Medical Schemes Act (MSA) (FinMark Trust, 2016). The aim of this study is to empirically evaluate the relationship between efficiency and competition in the medical scheme industry in South Africa from 2011 to 2021. In the medical scheme market, there are two types of medical schemes available: open medical schemes and closed or restricted medical schemes. Open medical schemes are available to anybody who chooses to enrol, while restricted medical schemes are only accessible to members of specific groups or entities, such as individual businesses, industries, or unions (Council for Medical Schemes [CMS], 2021). This study conducts an empirical evaluation of efficiency and competition in South African medical schemes from 2011 to 2021, specifically differentiating between open and restricted schemes. The research utilises an ordinary least squares regression model on panel data to find that closed medical schemes have greater efficiency at 98% than open medical schemes at 96.7%. Based on the Random Effects model output, the regression finds that there is a significant impact of competition (negative) and size of memberships (positive) in explaining some variation in the medical scheme industry, however the variables tested explained 40% of the variation in the regression. The findings reveal a complex situation in the market, marked by strong effectiveness, moderate market dominance, varied financial strategies and stable membership levels among closed medical schemes.